Effects of dietary supplement with a Chinese herbal mixture on growth performance, antioxidant capacity, and gut microbiota in weaned pigs - Xu, Qinglei; Cheng, Meng; Jiang, Rong; Zhao, Xianle; Zhu, Jianjin; Liu, Mingzheng; Chao, Xiaohuan; Zhang, Chunlei; Zhou, Bo (Frontiers in Veterinary Science, 2022)
Weaning stress decreases the growth performance of piglets and is one of the main concerns of pig industries. Traditional Chinese herbal medicines have been used to reduce the adverse effects of weaning stress as both nutritional supplements and antibiotic substitutes. This study aimed to evaluate the effects of a Chinese herbal mixture (Kangtaile, which contained Paeonia lactiflora, licorice, dandelion, and tea polyphenols) on the growth performances, immune response, antioxidant capacity, and intestinal microbiota of weaned pigs. A total of 400 weaned pigs [Duroc × (Landrace × Yorkshire)] were randomly allocated into one of four treatments: the CON group, fed with basic diet; the HM1 group, fed with basal diet supplemented with 0.5 g herbal mixture/kg diet; the HM2 group, fed with basal diet supplemented with 1.0 g herbal mixture/kg diet; or the HM3 group, fed with basal diet supplemented with 1.5 g herbal mixture/kg diet. The results revealed that dietary supplementation with the herbal mixture for 28 days improved average daily gain and decreased feed to gain and diarrhea frequency of weaned pigs. Moreover, dietary supple-mentation with the herbal mixture improved the antioxidant capacity through increasing the activity of catalase (CAT) and the total antioxidant capacity (T-AOC) level, while decreasing the concentration of malondialdehyde (MDA) in the serum. Pigs supplemented with herbal mixture presented an increased serum immunoglobulin (Ig)M level on day 14 compared with control pigs. The herbal mixture altered the composition of intestinal microbiota by influencing the relative abundances of Firmicutes and Bacteroidetes at the phylum level. The relative abundances of the Firmicutes and Bacteroidetes were significantly related to the body weight gain of pigs. In conclusion, supplementation of herbal mixture to the diet improved growth performance, immunity, and antioxidant capacity and modified the composition of intestinal microbiota in weaning pigs. This study provides new insights into the nutritional regulation effects of the herbal mixtures on weaned pigs.